Characterization of culturable airborne microorganisms in the Yucatan Peninsula. (15th February 2020) - Rodriguez-Gomez, Camila; Ramirez-Romero, Carolina; Cordoba, Fernanda; Raga, Graciela B.; Salinas, Eva; Martinez, Leticia; Rosas, Irma; Quintana, Erika T.; Maldonado, Luis A.; Rosas, Daniel; Amador, Talib; Alvarez, Harry; et al.
Abstract: The concentration of biological particles in the atmosphere is widely variable because it depends on several meteorological and geographical factors. Meteorological conditions in tropical coastal cities are unique due to both marine and terrestrial influences that can strongly modify the concentration and diversity of airborne microorganisms. Nevertheless, very few studies have been conducted in tropical coastal cities. This study presents the comparative results from four field campaigns carried out between 2017 and 2018 in two tropical cities located in the Yucatan Peninsula (Mexico): Sisal (a village right on the coast) and Merida (the State capital, 48 km from the coastline). The concentration of bacteria and fungal propagules, in colony-forming units or CFU per m 3, sampled in Merida and Sisal are not comparable despite their proximity (i.e., 48 km away); however, both show similar seasonality and inter-annual trends. The results indicate that terrestrial microbiota dominates over that of marine origin, and show that fungal propagules are the dominant microorganism present at both sites. Also, these results indicate that meteorological conditions in the rainy season are more favorable for the growth of microorganisms than dry cold conditions. The predominant culturable bacterial phylum sampled during the four field campaigns carried out in 2017 and 2018 in the Yucatan Peninsula were Actinobacteria, Firmicutes, and Proteobacteria. The fraction of bacteria that reacted to a Gram positive stain was 62% and to Gram negative 38%. The fungal propagules genera relative concentration varied between both sampling sites, with Cladosporium and Penicillium being the most common at the coast in Sisal and Aspergillus in Merida. Highlights: Airborne microorganism concentrations were higher during the rainy season and likely related to higher temperatures and RH. The long-range transport of microorganisms from other latitudes into the Yucatan Peninsula was confirmed. Fungal propagules were the most abundant microorganisms, with higher concentrations than bacteria and actinobacteria.